Population Dynamics of Pometia for The Period of Post-Selective Logging in Tropical Rainforest, Southern Papua, Indonesia - Murdjoko, Agustinus; Marsono, Djoko; Sadono, Ronggo; Hadisusanto, Suwarno (Biosaintifika: Journal of Biology & Biology Education, 2016)
Tropical rainforest changed in term of structure, composition and population, resulting from logging. One of target trees during logging is Pometia. Our goals of this research were to answer that (1) How were survival, growth, fecundity and population growth rate (?) of Pometia within remnant stands?; (2) what were driving factors to explain population dynamics of Pometia within logged forest?. Data were derived from three hectares-permanent sample plot (PSP) in logged forest of PT Tunas Timber Lestari. Integral Projection Models (IPMs) were applied to analyze population dynamics. The study showed dynamically that probability of the individuals of Pometia survived in this area did not significantly differ among their size, while stands showed the significant difference between small and large individuals. The growth of both individuals of Pometia and stands varied significantly in different size. The probability of fecundity both Pometia and stands were significantly different among size. The population of Pometia has been increasing for about a decade as the population of all stands was growing as well. Moreover, the regular documentation of species composition and structure before and after logging is necessary as a control of biodiversity. Therefore, a proper protocol to monitor the biodiversity should be designed by government and disseminated it to logging companies. How to CiteMurdjoko, A., Marsono, D., Sadono, R. & Hadisusanto, S. (2016). Population Dynamics of Pometia for The Period of Post-Selective Logging in Tropical Rainforest, Southern Papua, Indonesia. Biosaintifika: Journal of Biology & Biology Education, 8(3), 321-330.